Anticoagulation and Antiplatelet Therapy in Contact Sports: Is it Career Limiting?. (March 2021) - Kichloo, Asim; Amir, Rawan; Wani, Farah; Randhawa, Sukhbir; Rudd, Benjamin; Rechlin, David
Medical conditions requiring treatment with anticoagulation (AC) or antiplatelet therapy have a huge burden on the average patient, but such conditions can have catastrophic effects on the careers of young, rising athletes, in particular those involved in contact sports at a professional level. Contact sports are defined as sports in which body-to-body contact is expected as part of the game such as football, basketball, soccer and hockey. The rates of injuries in these sports are high increasing the likelihood of bleeding event on AC. The main etiologies requiring AC and antiplatelets in athletes are venous thromboembolism and coronary artery disease, respectively. To date, there are no clear medical guidelines on the management of such conditions in athletes. Herein we review the traditional approach to treating such conditions afflicting athletes as well as more recently modified approaches to answer the ultimate question: should anticoagulation or antiplatelet therapy in contact sports be career limiting?